PERSEPSI MASYARAKAT TERHADAP KEGIATAN REHABILITASI HUTAN LINDUNG DI DESA SARUMBAYA KECAMATAN BANAWA SELATAN KABUPATEN DONGGALA - Abdi Tri Pambudi; Adam Malik; Andi Sahri Alam (Jurnal Warta Rimba, 2019)
Forest and land rehabilitation is intended to restore, maintain and improve forest and land functions so that the carrying capacity, productivity and role in supporting living systems is maintained. The reduced quality of the environment can lead to natural disasters such as floods and landslides and other natural disasters that can harm living things. This study aims to determine public perceptions of protected forest rehabilitation activities in Sarumbaya Village. The study was conducted for three months, from November 2016 to January 2017. The research location was located in Sarumbaya Village, Banawa Selatan District, Donggala Regency, Central Sulawesi Province. Data collection techniques through interviews using questionnaires, with in-depth interviews, which are expected to provide information that supports the validity of data obtained from the questionnaire results. The number of respondents taken was 32 people, respondents were chosen deliberately using a Likert scale analysis with scaling modifications 1-3-5. The results showed that the perception of Sarumbaya Village community towards the rehabilitation of protected forest activities carried out by the Donggala District Forestry Service can be categorized high. This is evident from the community's knowledge of the existence of rehabilitation activities and community involvement in rehabilitation activities starting from the planning, implementation and maintenance stages which are classified as high.Keywords: Perception, Rehabilitation, Protection Forest.